Radios et religions en Afrique subsaharienne. Dynamisme, concurrence, action sociale - Alexia Pilon Diabaté (Communiquer)
The book Radios et religions en Afrique subsaharienne is based on a study of religious radio in West Africa conducted by Étienne Damome between 2004 and 2013. The author describes and examines programming grids, content, audiences and the uses of the most important religious radios in Benin, Burkina Faso, Ghana and Togo. Through this analysis, he draws a portrait of the religious situation in Africa scarred by a revival of religious activism and competition.